Analysis of Environmental Management at the Container Terminal of PT Pelabuhan Indonesia (Pelindo) III Semarang - Regita Ardiati, Nirmala (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2024)
This study employs a qualitative approach using a descriptive method. Primary data is obtained through observation, interviews, and documentation, while secondary data is derived from environmental management implementation reports. The data collected is then evaluated for compliance with environmental management regulations, including Law No. 32 of 2009 on Environmental Protection and Management, Government Regulation No. 101 of 2014 on the Management of Hazardous and Toxic Waste Materials, and ISO 14001:2015 on Environmental Management Systems. According to the research findings, environmental management at PT Pelindo III Container Terminal in Semarang is supervised by a certified ecological expert within the HSSE (Health et al.) department. The company manages hazardous liquid waste, air emissions, and hazardous and non-hazardous solid waste. However, non-hazardous liquid waste and dust emissions have not been monitored and managed. The company received a PROPER certification in 2018 and an ISO 14001:2015 certification in 2015 for its environmental management.